Low-loss manganese-zinc soft magnetic ferrite material suitable for broadband and wide-temperature range and preparation method of low-loss manganese-zinc soft magnetic ferrite material
By optimizing the composition ratio and sintering process of manganese zinc soft ferrite materials, the problem of difficult material to achieve low loss in a wide range of bandwidth and temperature is solved, and high efficiency application at different powers and temperatures is achieved.
Patent Information
- Application Number
- CN202411687779.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
AI Technical Summary
Existing manganese zinc soft ferrite materials are difficult to meet the high efficiency requirements at different power and temperatures at the same time, especially in a wide range of bandwidth and temperatures, which are difficult to achieve low losses.
By optimizing the ratio of components such as Fe2O3, ZnO, Co3O4, SnO2, etc., combined with appropriate additives such as SiO2, CaCO3, ZrO2 and Nb2O5, the sintering process parameters are strictly controlled to form a material with low magnetic crystal anisotropy and high resistivity.
It realizes the low loss characteristics of manganese zinc soft ferrite material in the range of 25-120°C and 100-300kHz, and the power consumption is 270-370kW/m3, which is suitable for low loss electronic transformers.
Smart Images

Figure BDA0005150067280000041 
Figure BDA0005150067280000051 
Figure BDA0005150067280000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft ferrite materials, and in particular relates to a low-loss manganese-zinc soft ferrite material suitable for wide frequency and temperature range and a preparation method thereof. Background Art
[0002] The smaller the absolute value of magnetocrystalline anisotropy |K1| of manganese-zinc soft ferrite, the lower the hysteresis loss, the lower the resistivity, and the lower the eddy current loss. Low-frequency power consumption is mainly hysteresis loss. As the frequency increases, the eddy current loss increases. Reducing hysteresis loss and eddy current loss can significantly improve the total loss of the material. In manganese-zinc soft ferrite materials, the positive distribution of MnZn ferrite K1 is less than 0, and the effect of ferrous ions on K1 value is positive. Therefore, an appropriate amount of ferrous ions can positively compensate for |K1|, making |K1| closer to 0, thereby reducing losses.
[0003] In the prior art, patent document CN115073158A increases the cutoff frequency of the material by using the main component with a low zinc oxide ratio, thereby increasing the applicable frequency range of the material and reducing high-frequency power consumption, achieving a loss of 230-330kW / m at 25-120°C, 300kHz and 100mT. 3 However, it is not suitable for lower frequency application scenarios. It is necessary to increase the zinc oxide ratio and reduce the hysteresis loss at low frequency. At the same time, although excessive sintering oxygen content and low iron oxide content can increase the resistivity and reduce eddy current loss, it will cause the ferrous ions to further decrease, thereby increasing |K1|, which is not conducive to the improvement of low-frequency 100kHz power consumption. Patent document CN102390988A increases the zinc oxide content of the main component, but excessive iron oxide content will lead to increased resistivity, which is manifested as increased temperature and a sharp increase in power consumption. Although the power consumption is reduced to 198kW / m at 25°C, 300kHz and 100mT, 3 However, even if the sintering temperature is reduced to 1200℃, the power loss at 100℃ still increases to 390kW / m 3 At the same time, too high an iron oxide content will inevitably lead to over-compensation of magnetocrystalline anisotropy, and |K1| will increase, resulting in increased hysteresis loss. Patent document CN104591711A uses iron oxide, zinc oxide, and cobalt oxide to coordinately regulate the magnetocrystalline anisotropy of the material, reducing the loss to 270-380kW / m at 25-160°C, 100kHz, and 200mT. 3 However, too long a holding time will inevitably lead to excessive growth of grains, resulting in reduced resistivity and cutoff frequency, thus worsening high-frequency power consumption.
[0004] In summary, the current progress in improving the low-loss properties of manganese-zinc soft ferrites suitable for a wide frequency and temperature range is slow, and it is difficult to simultaneously meet the high-efficiency requirements of electronic transformers at different powers and temperatures. It is urgent to develop a low-loss manganese-zinc soft ferrite material suitable for 25-120°C and 100-300kHz. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the main purpose of the present invention is to provide a low-loss manganese-zinc soft ferrite material suitable for a wide frequency band and a wide temperature range.
[0006] Another object of the present invention is to provide a method for preparing the low-loss manganese-zinc soft ferrite material.
[0007] Another object of the present invention is to provide the use of the low-loss manganese-zinc soft ferrite material in the preparation of a low-loss electronic transformer suitable for use within 25 to 120° C. and 100 to 300 kHz.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] The first aspect of the present invention provides a low-loss manganese-zinc soft ferrite material suitable for wide frequency and wide temperature, comprising a main component, a first type of additive, a second type of additive and a third type of additive, wherein:
[0010] The main components are as follows: Fe2O3: 71.25% to 71.5%, ZnO: 6.0% to 7.5%, and the balance is MnO;
[0011] The first type of additives are used to adjust magnetocrystalline anisotropy, and include, in terms of mass percentage of the main component: Co3O4: 0.4% to 0.5%, SnO2: 0.07% to 0.11%;
[0012] The second type of additives are used to form a high resistance coating layer and refine grains, and include, in terms of mass percentage of the main component: SiO2: 0.004% to 0.008%, CaCO3: 0.03% to 0.04%, ZrO2: 0.01% to 0.02%;
[0013] The third type of additives are used to promote pore healing and reduce micro defects, and include, in terms of mass percentage of the main component: Nb2O5: 0.02% to 0.03%.
[0014] In terms of composition, the low-loss manganese-zinc soft ferrite material achieves low-loss characteristics of manganese-zinc soft ferrite materials in a wide temperature and frequency range by optimizing the ratio of Fe2O3, ZnO, Co3O4, and SnO2, and strictly controlling the content of each component, wherein: if the Fe2O3 content is too high or too low, the magnetocrystalline anisotropy |K1| will increase, and the overall loss will increase; if the Fe2O3 content is too high, the resistivity will decrease, and the high-temperature power consumption will increase rapidly. The first type of additive Co3O4 content is reasonably matched with the main component. If it is too high or too low, the |K1| value cannot be balanced, resulting in an increase in power consumption; SnO2 can reduce the |K1| value by regulating ferrous ions, while increasing the internal resistivity of the grain boundary and reducing the overall power consumption. The second type of additives SiO2 and CaCO3 can form an insulating layer with high resistivity at the grain boundary to reduce eddy current loss; ZrO2 can refine the grains and reduce eddy current loss. The third type of additive Nb2O5 can promote the pore filling of ZnO volatilization during the sintering process, reducing the porosity and hysteresis loss.
[0015] The second aspect of the present invention provides a method for preparing the low-loss manganese-zinc soft ferrite material, comprising the following steps:
[0016] (1) weighing Fe2O3, MnO and ZnO raw materials according to the ratio of the main components, mixing and pre-calcining to obtain a pre-calcined material;
[0017] (2) The pre-sintered material is first coarsely crushed, and then the first type of additive, the second type of additive and the third type of additive are added to perform sand grinding and fine grinding to obtain a sand abrasive; then a PVA binder is added and spray granulation is performed to obtain a granular material;
[0018] (3) The granular material is sintered in a mixed atmosphere of nitrogen and oxygen to obtain the granular material.
[0019] Preferably, in step (1), the pre-firing temperature is 850-900° C., and the pre-firing time is 1-2 hours.
[0020] Preferably, in step (2), the particle size of the abrasive is 1.3 to 1.9 μm.
[0021] Preferably, in step (2), the spray flow rate of the spray granulation is 2000-2200 kg / h, and the spray temperature is 240-280°C.
[0022] Preferably, in step (3), the sintering temperature is 1250-1280° C., and the sintering holding time is 4-5 h.
[0023] Preferably, in step (3), the oxygen content during the sintering temperature increase process is below 0.1%.
[0024] Preferably, in step (3), the oxygen content during the sintering and heat-insulating process is between 1.25% and 3.0%.
[0025] In the preparation method of the low-loss manganese-zinc soft magnetic ferrite material, a suitable pre-sintering temperature is selected to ensure a certain sintering activity, improve the sintering density and avoid uneven grain growth; sand grinding is controlled to achieve a reasonable particle size distribution to ensure sintering activity, refine the grains and avoid uneven grain production; sintering is controlled within a reasonable temperature range and insulation time to allow the grains to grow fully and refine the grains; sintering is controlled to have a reasonable oxygen content to control the ferrous ion content in the components while improving the surface resistance; and during the sintering temperature rise process, a low oxygen content is controlled to promote grain growth, improve sintering density and reduce microscopic defects.
[0026] The third aspect of the present invention provides the use of the low-loss manganese-zinc soft ferrite material in the preparation of a low-loss electronic transformer suitable for use within 25 to 120° C. and 100 to 300 kHz.
[0027] Compared with the prior art, the present invention has the following beneficial effects: by reasonably controlling the content ratio of Fe2O3, ZnO, Co3O4, SnO2 and other components, strictly controlling the sand grinding particle size and sintering process parameters, the wide-band, wide-temperature and low-loss manganese-zinc ferrite material can be achieved. Under the conditions of 100kHz and 200mT, the power consumption is 270-370kW / m at 25-120℃. 3 At the same time, under the conditions of 300kHz and 100mT, the power consumption is between 230 and 360kW / m at 25 to 120℃. 3 , and has good application prospects for low-loss electronic transformers. DETAILED DESCRIPTION
[0028] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that for those of ordinary skill in the art, several changes and improvements made without departing from the concept of the present invention all belong to the protection scope of the present invention.
[0029] Example 1
[0030] This embodiment provides a manganese-zinc ferrite material, including a main component of iron-manganese-zinc oxide and an additive, wherein the main component is, by mass percentage, 71.46% Fe2O3, 6.3% ZnO, and the remainder is MnO;
[0031] The first type of additives, calculated by mass percentage of the main components, are: Co3O4: 0.43%, SnO2: 0.1%;
[0032] The second type of additives, calculated by mass percentage of the main components, are: SiO2: 0.004%, CaCO3: 0.035%, ZrO2: 0.01%;
[0033] The third type of additives, in terms of mass percentage of the main components, is: Nb2O5: 0.03%.
[0034] The preparation method of the manganese-zinc ferrite material comprises the following steps:
[0035] (1) Fe2O3, MnO and ZnO raw materials are weighed and mixed according to the main component ratio, and pre-calcined at 900°C for 1 hour to obtain a pre-calcined material;
[0036] (2) The pre-sintered material is coarsely crushed, and then the first, second and third additives are added, and then finely crushed by sand milling. The obtained sand mill particle size D50 is 1.6 μm. After adding PVA binder, spray granulation is performed at a spray flow rate of 2100 kg / h and a spray temperature of 270° C. to obtain a granular material;
[0037] (3) The pellets are sintered in a nitrogen and oxygen mixed atmosphere at a sintering temperature of 1270° C. The sintering holding time is 5 hours. The oxygen content is controlled below 0.01% during the sintering heating process at 900-1250° C. and the oxygen content is controlled at 1.5% during the sintering holding process.
[0038] Comparative Example 1
[0039] Comparative Example 1: A manganese-zinc ferrite material is prepared. The material composition and preparation method are the same as those of Example 1, except that the particle size of the abrasive is 1.17 μm.
[0040] Comparative Example 2
[0041] Comparative Example 2: A manganese-zinc ferrite material is prepared. The material composition and preparation method are the same as those of Example 1, except that the particle size of the abrasive is 2.06 μm.
[0042] Example 1, Comparative Example 1 and Comparative Example 2 used SY8218 BH analyzer to measure power loss (Pcv, kW / m 3 ) performance test, the results are shown in Table 1.
[0043] Table 1
[0044]
[0045] As shown in Table 1, the sanding particle size of Comparative Example 1 and Comparative Example 2 is too fine or too coarse, resulting in incomplete or uneven grain growth during the sintering process, which leads to serious deterioration of hysteresis loss and increased power consumption at 100kHz; the particle size of Comparative Example 2 is relatively coarse, but the increase at 300kHz is relatively small, which is mainly because the impact of hysteresis loss on power consumption at 300kHz is smaller than that at 100kHz.
[0046] Example 2
[0047] This embodiment provides a manganese-zinc ferrite material, including a main component of iron-manganese-zinc oxide and an additive, wherein the main component is, by mass percentage, 71.45% Fe2O3, 6.18% ZnO, and the remainder is MnO;
[0048] The first type of additives, calculated by mass percentage of the main components, are: Co3O4: 0.43%, SnO2: 0.1%;
[0049] The second type of additives, calculated by mass percentage of the main components, are: SiO2: 0.008%, CaCO3: 0.04%, ZrO2: 0.01%;
[0050] The third type of additives, calculated by mass percentage of the main components, is: Nb2O5: 0.03%.
[0051] The preparation method of the manganese-zinc ferrite material comprises the following steps:
[0052] (1) Fe2O3, MnO and ZnO raw materials are weighed and mixed according to the main component ratio, and pre-calcined at 900°C for 1 hour to obtain a pre-calcined material;
[0053] (2) The pre-sintered material is coarsely crushed, and then the first, second and third additives are added, and then finely crushed by sand milling. The obtained sand mill particle size D50 is 1.48 μm. After adding PVA binder, spray granulation is performed at a spray flow rate of 2100 kg / h and a spray temperature of 270° C. to obtain a granular material;
[0054] (3) The pellets are sintered in a nitrogen and oxygen mixed atmosphere at a sintering temperature of 1270° C. The sintering holding time is 4 hours. The oxygen content is controlled below 0.01% during the sintering heating process at 900-1250° C. and the oxygen content is controlled at 1.5% during the sintering holding process.
[0055] Comparative Example 3
[0056] Comparative Example 3: A manganese-zinc ferrite material is prepared, the main components of which are Fe2O3: 71.24%, ZnO: 6.18%, and the balance is MnO. The remaining material components and preparation method are the same as those in Example 2.
[0057] Comparative Example 4
[0058] Comparative Example 4: A manganese-zinc ferrite material is prepared, the main components of which are Fe2O3: 71.56%, ZnO: 6.18%, and the balance is MnO. The remaining material components and preparation method are the same as those in Example 2.
[0059] The performance tests of Example 2, Comparative Example 3 and Comparative Example 4 were performed using a SY8218 BH analyzer. The results are shown in Table 2.
[0060] Table 2
[0061]
[0062] As shown in Table 2, if the Fe2O3 content of Comparative Example 3 and Comparative Example 4 is too low or too high, it will lead to an increase in magnetocrystalline anisotropy |K1| and an increase in overall loss. If the Fe2O3 content of Comparative Example 4 is too high, it will also lead to a decrease in resistivity and a rapid increase in high-temperature power consumption. The power consumption at 100kHz increases more than that of Comparative Example 3, but the Fe2O3 content is beneficial to improving the cutoff frequency and operating frequency of the material. Therefore, the increase in loss at 300kHz in Comparative Example 4 is smaller than that in Comparative Example 3.
[0063] Example 3
[0064] This embodiment provides a manganese-zinc ferrite material, including a main component of iron-manganese-zinc oxide and an additive, wherein the main component is, by mass percentage, 71.35% Fe2O3, 7.1% ZnO, and the remainder is MnO;
[0065] The first type of additives, calculated by mass percentage of the main components, are: Co3O4: 0.4%, SnO2: 0.1%;
[0066] The second type of additives, calculated by mass percentage of the main components, are: SiO2: 0.008%, CaCO3: 0.04%, ZrO2: 0.02%;
[0067] The third type of additives, calculated by mass percentage of the main components, is: Nb2O5: 0.25%.
[0068] The preparation method of the manganese-zinc ferrite material comprises the following steps:
[0069] (1) Fe2O3, MnO and ZnO raw materials are weighed and mixed according to the main component ratio, and pre-calcined at 900°C for 1 hour to obtain a pre-calcined material;
[0070] (2) The pre-sintered material is coarsely crushed, and then the first, second and third additives are added, and then finely crushed by sand milling. The obtained sand mill particle size D50 is 1.8 μm. After adding PVA binder, spray granulation is performed at a spray flow rate of 2100 kg / h and a spray temperature of 270° C. to obtain granular material;
[0071] (3) The pellets are sintered in a nitrogen and oxygen mixed atmosphere at a sintering temperature of 1260° C. The sintering holding time is 5 hours. The oxygen content is controlled below 0.01% during the sintering heating process at 700-1250° C. and the oxygen content is controlled at 1.5% during the sintering holding process.
[0072] Example 4
[0073] This embodiment provides a manganese-zinc ferrite material, the main components of which are Fe2O3: 71.3%, ZnO: 7.3%, and the balance is MnO. The remaining material components and preparation method are the same as those in Example 3.
[0074] Example 5
[0075] This embodiment provides a manganese-zinc ferrite material, the main components of which are Fe2O3: 71.25%, ZnO: 7.5%, and the balance is MnO; the additive is Co3O4: 0.45% in terms of mass percentage of the main components, and the remaining material components and preparation methods are the same as those in Example 3.
[0076] Comparative Example 5
[0077] This embodiment provides a manganese-zinc ferrite material, the main components of which are: Fe2O3: 71.66%, ZnO: 5.2%, and the balance is MnO; the additive is Co3O4: 0.39% in terms of mass percentage of the main component, and the remaining material components and preparation methods are the same as those in Example 3.
[0078] Comparative Example 6
[0079] This embodiment provides a manganese-zinc ferrite material, the main components of which are: Fe2O3: 71.3%, ZnO: 7.3%, and the balance is MnO; the additive is Co3O4: 0.36% in terms of mass percentage of the main components, and the remaining material components and preparation methods are the same as those in Example 3.
[0080] The performance of Example 3, Example 4, Example 5, Comparative Example 5 and Comparative Example 6 was tested using the SY8218 BH analyzer, and the results are shown in Table 3.
[0081] Table 3
[0082]
[0083]
[0084] As can be seen from Table 3, Examples 3 to 5 reduce the resistivity by reducing the iron oxide content, thereby achieving the purpose of reducing eddy current losses. At the same time, increasing the zinc oxide content reduces the |K1| value to ensure low power consumption at room temperature, because simply reducing the iron oxide content will cause the total |K1| minimum point to move to high temperature, causing the power consumption at room temperature to deteriorate, and the overall power consumption will increase in serious cases (Table 2). In addition, although increasing the zinc oxide content in the formula can obtain a lower |K1| in the low temperature section, if it is not combined with increasing Co3O4 for high temperature |K1| compensation, it will cause the high temperature |K1| to increase, as shown in Comparative Example 6. Comparative Example 5 uses a low zinc formula to increase the cutoff frequency to reduce high-frequency losses, and it is necessary to increase the iron oxide content accordingly to reduce the |K1| value. However, the improvement in the |K1| value of the high-iron and low-zinc formula is limited, and the hysteresis loss is difficult to reduce, so it is difficult to improve the 100kHz power consumption.
[0085] Example 6
[0086] This embodiment provides a manganese-zinc ferrite material. In the preparation method, the sintering temperature is 1280° C., the oxygen content during the insulation process is 2.25%, and the material composition and other preparation methods are the same as those in Example 1.
[0087] Comparative Example 7
[0088] This comparative example provides a manganese-zinc ferrite material. In the preparation method, the sintering temperature is 1300° C., the oxygen content during the insulation process is 2.25%, and the material composition and other preparation methods are the same as those in Example 1.
[0089] Comparative Example 8
[0090] This comparative example provides a manganese-zinc ferrite material. In the preparation method, the sintering temperature is 1350° C., the oxygen content during the insulation process is 5.5%, and the material composition and other preparation methods are the same as those in Example 1.
[0091] The performance of Example 1, Example 6, Comparative Example 7 and Comparative Example 8 was tested using SY8218 BH analyzer, and the results are shown in Table 4.
[0092] Table 4
[0093]
[0094]
[0095] As shown in Table 4, when the sintering temperature is increased to 1300°C, although the 100kHz power consumption of Comparative Example 7 is improved, the large grain production causes the 300kHz power consumption to deteriorate. This deterioration becomes more obvious when the sintering temperature continues to rise, as described in the performance of Comparative Example 8.
[0096] Example 7
[0097] This embodiment provides a manganese-zinc ferrite material. In the preparation method, the oxygen content in the heat preservation process is 1.25%. The material composition and other preparation methods are the same as those in Example 1.
[0098] Example 8
[0099] This embodiment provides a manganese-zinc ferrite material. In the preparation method, the oxygen content in the heat preservation process is 2%. The material composition and other preparation methods are the same as those in Example 1.
[0100] The performance of Example 1, Example 7 and Example 8 was tested using SY8218 BH analyzer, and the results are shown in Table 5.
[0101] Table 5
[0102]
[0103] As shown in Table 5, when the oxygen content during the sintering and heat-insulating process of Example 1, Example 7, and Example 8 was between 1.25% and 1.5%, the overall performance was relatively stable.
[0104] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low-loss manganese-zinc soft ferrite material suitable for wide frequency band and wide temperature, characterized in that: It includes the main component, and also includes the first type of additives, the second type of additives and the third type of additives, among which: The main components are as follows: Fe2O3: 71.25% to 71.5%, ZnO: 6.0% to 7.5%, and the balance is MnO; The first type of additives are used to adjust magnetocrystalline anisotropy, and include, in terms of mass percentage of the main component: Co3O4: 0.4% to 0.5%, SnO2: 0.07% to 0.11%; The second type of additives are used to form a high resistance coating layer and refine grains, and include, in terms of mass percentage of the main component: SiO2: 0.004% to 0.008%, CaCO3: 0.03% to 0.04%, ZrO2: 0.01% to 0.02%; The third type of additives are used to promote pore healing and reduce micro defects, and include, in terms of mass percentage of the main component: Nb2O5: 0.02% to 0.03%.
2. The method for preparing the low-loss manganese-zinc soft ferrite material according to claim 1, characterized in that: The steps include: (1) weighing Fe2O3, MnO and ZnO raw materials according to the main component ratio, mixing and pre-calcining to obtain a pre-calcined material; (2) the pre-sintered material is firstly coarsely crushed; then the first type of additive, the second type of additive and the third type of additive are added and finely crushed by sand milling to obtain a sand abrasive; then a binder is added and spray granulation is performed to obtain a granular material; (3) The granular material is sintered in a mixed atmosphere of nitrogen and oxygen to obtain the granular material.
3. The method for preparing the low-loss manganese-zinc soft ferrite material according to claim 2, characterized in that: In step (1), the pre-firing temperature is 850-900° C., and the pre-firing time is 1-2 hours.
4. The method for preparing the low-loss manganese-zinc soft ferrite material according to claim 2, characterized in that: In step (2), the abrasive particle size is 1.3 to 1.9 μm.
5. The method for preparing the low-loss manganese-zinc soft ferrite material according to claim 2, characterized in that: In step (3), the sintering temperature is 1250-1280° C., and the sintering holding time is 4-5 hours.
6. The method for preparing the low-loss manganese-zinc soft ferrite material according to claim 2, characterized in that: In step (3), the oxygen content during the sintering temperature increase process is below 0.1%.
7. The method for preparing the low-loss manganese-zinc soft ferrite material according to claim 2, characterized in that: In step (3), the oxygen content during the sintering and heat preservation process is between 1.25% and 3.0%.
8. Use of the low-loss manganese-zinc soft ferrite material according to claim 1 in the preparation of a low-loss electronic transformer suitable for use in a temperature range of 25 to 120°C and 100 to 300 kHz.
Citation Information
Patent Citations
Wide-temperature-range low-loss Mn-Zn ferrite specially used for solar energy inverter, and preparation method thereof
CN102390988A
Low-loss manganese zinc ferrite material for temperature of 40 DEG C below zero to 160 DEG C and manufacturing method thereof
CN104591711A
Manganese zinc ferrite material as well as preparation method and application thereof
CN115073158A
Cited By
Wide-temperature low-loss manganese zinc ferrite material as well as preparation method and application thereof
CN121698648A
Wide-temperature low-loss manganese-zinc ferrite material, preparation method and application thereof
CN121698648B